Human Resource, Culture and Innovation as The Success Factors of The Coastal Tourism Community Objects - Arie Frits Kawulur; Ramon Arthur Ferry Tumiwa; Merry Christie Natalia Rumagit (Journal of International Conference Proceedings (JICP), 2020)
Currently the central government and government of North Sulawesi Province are actively doing implementation of infrastructure development, especially, infrastructure development which connects with coastal tourism area in North Minahasa regency, Indonesa. Therefore, it is necessary to look that impact on tourism and coastal community’s economics growth. This purposed of study were to analyze the factors of human resources, ‘Mapalus’ culture and technological and product innovations. Those factors indicated could strengthen the sustainability of community businesses around the coastal tourism at North Minahasa, North Sulawesi Province, Indonesia. The method was used in this research is a qualitative method. Data were collected with in-depth interview to several key informants and community business in the vicinity of North Minahasa Regency coastal tourism objects. The results showed that the factor of human resources play an important role in community entrepreneurship groups, such as ownership and business integrity. Research also figure out some business groups have not succeeded yet, even though they were supposed had enough knowledge, experience and skills due of some of them were the participants of entrepreneurship upgrading. The cultural value of ‘Mapalus’ were also always seen when the one group of fishermen go out to sea. However, from the research discover surprising result, the value of ‘Mapalus’ culture has been missing their noble value. That fact, seen from the cultural values has begun to erode due to the development of villages which are valued more with financial exchange. The technology and product innovation capabilities factors in the coastal areas are still low and need to be improved. The results indicate coastal business community need of presence of the expert assistants to increase technology and product innovation capabilities.